Profile of the adult population of the city of Corrientes (Argentina) in relation to dental health insurance - Dho, María Silvina (2017)
Objective: To characterize the adult population of the city of Corrientes (Argentina) in relation to dental health insurance according to sociodemographic and dental variables. Materials and Methods: A descriptive cross-sectional study was conducted in the city of Corrientes (Argentina). Information regarding the study variables was collected through the application of a structured survey. Sample size was determined by establishing a 95% confidence level (381 subjects between 35 and 44 years of age). The direct face-to-face observation technique was used for data collection. A simple random sample design was applied for the selection of the homes to be surveyed, which was complemented by a non-probabilistic sampling using quotas for the selection of the individuals to be interviewed from the 2010 Population Census data. Results: Of the total of the participants, 56.4% had dental health insurance. Health insurance was significantly associated with a higher socioeconomic level OR: 1.90 (95% CI 1.26-2.87, p=0.01); greater probability of having had a consultation in the 12 months prior to the interview OR: 1.74 (95% CI 1.13-2.68, p=0.01), going to the dentist for dental treatments OR: 1.5 (95% CI 1.02-2.43, p=0.03), or because of pain or an emergency problem OR: 1.59 (95% CI 1.05- 2.42, p=0.02), and presenting better oral hygiene self-care. Conclusions: There are oral health inequities in the adult population of the city of Corrientes (Argentina). Having dental health insurance is associated with a higher socioeconomic level, having more frequent dental consultations to get dental treatment and in emergency situations, as well as presenting better oral hygiene self-care.